Assess the effectiveness of the self-instructional module (SIM) on the knowledge of coronary artery disease (CAD) and its prevention among the employees of selected banks at Gwalior - Faurkh Khan, Mr. (International Journal of Nursing Research, 2023)
The WHO expert committee on prevention of Coronary Artery Disease identified a number of lifestyles and environmental factors as the underlying causes of a CAD. These risk factors may be conceptualized as modifiable and no modifiable. A sedentary lifestyle is associated with a greater risk of the development of early CHD. The risk for cardiovascular diseases increases among bank employees with a sedentary lifestyle. Therefore Aim of the study was to determine the level of knowledge on CAD and its prevention among bank employees before & after administration of SIM. Material and methods of study were as the Descriptive evaluative approach was used and the study was carried out in six selected banks in Gwalior. The research design was pre-experimental one group pre-test post-test design. The sample comprised of 50 bank employees from the selected banks. The banks were selected by convenience sampling technique whereas employees were selected by purposive sampling technique. The data collection was done from 01/10/16 to 23/10/16. Data were collected by administering a structured knowledge questionnaire before and after the administration of SIM. The data were analyzed using descriptive and inferential statistics. The study Results showed that bank employees, in general, lacked knowledge on CAD and especially on prevention aspect. The mean knowledge score was 10.56. There was a marked gain in mean knowledge score after administration of SIM (23.54). The difference in mean knowledge score was statistically significant at 0.05 level‘t’ (49) =23.35. Hence the findings of this study support the need for conducting health camps and awareness programme on CAD and its prevention to the bank employees. Conclusion: The findings of this study shows that the SIM was effective in terms of gaining knowledge on CAD and its prevention among bank employees (t49=23.35, P < 0.05).